Exploring the Influence of Novelty Seeking and Perceived Safety on Tourist Loyalty through Well-being: A Case Study of Tangkahan - Nasib; Sharina Osman; Muhammad Fathoni (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study investigates the role of novelty seeking and perceived safety in influencing tourist loyalty through well-being at the Tangkahan tourist attraction. A total of 400 questionnaires were distributed, and 396 completed questionnaires were used for analysis. This study uses partial least squares-based structural equation modeling (PLS-SEM) to validate and estimate the proposed research model, using Smart-PLS software to analyze data and estimate the relationship between latent variables. The estimation results indicate that novelty seeking and perceived safety have a positive and significant effect on tourist well-being, which in turn affects tourist loyalty. This study also revealed differences in the levels of novelty seeking and perceived safety among tourists with different demographic characteristics. In addition, the analysis results indicated that tourists who seek new experiences are more likely to experience an increase in well-being, which in turn increases tourist loyalty to Tangkahan tourist attractions